2015
DOI: 10.1111/acem.12797
|View full text |Cite
|
Sign up to set email alerts
|

The Urban Emergency Department: A Potential Increased Occupational Hazard for Sharps‐related Injuries

Abstract: Objectives: Health care workers are at risk for sharps-related injuries while working in the clinical arena. The authors sought to quantify and compare the frequency of these injuries for all health care personnel between the urban and community emergency department (ED).Methods: A retrospective review was performed on the institutional human resources database of all self-or supervisor-reported sharps-related injuries that occurred to ED personnel in a single health system from January 2010 through September … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 9 publications
0
7
0
1
Order By: Relevance
“…This result has not been described previously and is surprising, since within their profession physicians have more invasive activities than nurses. Studies also show that physicians, for example, are more affected by needlestick injuries than nurses [74, 75]. Therefore, we cannot explain why nurses in our sample indicated occupational risks more often than physicians.…”
Section: Discussionmentioning
confidence: 73%
“…This result has not been described previously and is surprising, since within their profession physicians have more invasive activities than nurses. Studies also show that physicians, for example, are more affected by needlestick injuries than nurses [74, 75]. Therefore, we cannot explain why nurses in our sample indicated occupational risks more often than physicians.…”
Section: Discussionmentioning
confidence: 73%
“…HCWs in urban EDs face higher risk for sharps injuries compared to community EDs with rates of 20.3 versus 5.9 per 100,000 patient visits, respectively ( p <0.001). 27 The environment in EDs is fast-paced and often unpredictable, in addition to often unknown source status, thus increasing the risk of NSIs and their consequences.…”
Section: Resultsmentioning
confidence: 99%
“…16 Beyond violence, a study showed that 55%-70% of emergency physicians experienced at least 1 needlestick, and that many (44%) of the 171 sharp injuries in an ED during a 4-year period were suffered by physicians. 17 The risk of infection transmission among healthcare workers was also high during public health outbreaks (eg., the 2009 H1N1 pandemic, the SARS, and Middle East respiratory syndrome outbreak), underscoring the importance of proper PPE. During the first wave of the H1N1 pandemic, Kumar et al reported that 18.5% of ED healthcare workers were seropositive for H1N1.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, about 78% of emergency physicians experienced at least 1 violent act over a 1‐year period, with 21% of those incidents being physical assault 16 . Beyond violence, a study showed that 55%–70% of emergency physicians experienced at least 1 needlestick, and that many (44%) of the 171 sharp injuries in an ED during a 4‐year period were suffered by physicians 17 . The risk of infection transmission among healthcare workers was also high during public health outbreaks (eg., the 2009 H1N1 pandemic, the SARS, and Middle East respiratory syndrome outbreak), underscoring the importance of proper PPE.…”
Section: Discussionmentioning
confidence: 99%